An exact calculation method for Gini coefficient and its application in China. (18th August 2018) - Chen, Li-Shuang; Huang, Qi
Abstract: Although there are many methods for calculating the Gini coefficient, but most of them are ultimately applied to Chinese practice through some kind of approximation means. A more accurate calculation method of N-aliquot part Gini coefficient is obtained and applied to Chinese practice through a rigorous mathematical derivation in this paper. It is found that the Gini coefficients in urban areas, rural areas and the whole China have obvious inverted U-shaped characteristics; it is an apparent turning point in 2008. At the same time, the population-weighted contribution rate study shows, the contribution rate has continued to increase from 14.3% in 2000 to 32.8% in 2015 to the national Gini coefficient coming from the urban group, however it has continued to fall from 23.8% to 8.7% coming from rural areas.